DEVELOPING THE SERVICE FIELD IMPROVING THE MECHANISMS OF EFFECTIVE USE OF STATE SUBSIDIES AND ASSISTANCE (Conferencea, 2024)
The role of small enterprises in providing employment in the so-called “dormitory” areas, in which the majority of residents do not work at their place of residence, is noticeable. Small businesses in such areas are characterized by specialization in activities in the service sector, which were previously carried out within the family. The purpose of the work is to explore the system and effectiveness of supporting small business in the service sector in Uzbekistan and its constituent entities.